Passivity enforced circuit model of frequency‐domain responses with source elements. (5th October 2016) - Su, Donglin; Li, Bing; Wang, Junjun; Song, Xinwei
Abstract: This paper presents an equivalent circuit model with source elements for systems containing external field. The coupling effect of the external field is considered with current sources ( I s ) added to the expression of admittance matrix ( Y ) of the system. The frequency‐domain responses of Y and I s could be fit to the rational polynomials with vector fitting method and then converted to equivalent circuits with the proposed method. As the dual quantities of Y and I s, the circuit extraction method from Z and V s is also introduced. Passivity enforcement of the RLC elements in the circuits is realized with the optimization method. A novel circuit structure for the multi‐port system is proposed with this method based on the equivalence of the field‐port coupling and port‐port coupling. The proposed model is demonstrated to be effective to extract the equivalent circuits of the multiconductor transmission line system under an incident wave.